1984
DOI: 10.1161/01.str.15.2.275
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mild hypercapnia on somatosensory evoked potentials in experimental cerebral ischemia.

Abstract: In a previous report, the authors demonstrated the effectiveness of mild hypercapnia in enhancing decreased perfusion flow in ischemic, non-infarcted brain tissues. However, the previous work lacked in verification of improvement of suppressed brain function. Therefore, this report was attempted to evaluate the effect of hypercapnia on somatosensory evoked potential (SEP), using the similar ischemic model as previously. The results showed that mild hypercapnia of 43 to 55 mm Hg range was beneficial not only fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Both hypercapnia and hypocapnia have been proposed as an intervention to improve the outcomes of cerebral ischemia (see (Brian, 1998) for a review). The researchers proposing hypercapnia reason that inhalation of CO 2 would increase the blood supply to the ischemia regions, thus would benefit the ischemic regions (Nakagawa et al, 1984). However, other researchers argue that vessels in ischemic regions cannot be further dilated by hypercapnia and, when the surrounding normal vessels dilate in response to CO 2 , the blood flow to the ischemic brain may actually decrease, often referred to as a vascular steal phenomenon (Brian, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Both hypercapnia and hypocapnia have been proposed as an intervention to improve the outcomes of cerebral ischemia (see (Brian, 1998) for a review). The researchers proposing hypercapnia reason that inhalation of CO 2 would increase the blood supply to the ischemia regions, thus would benefit the ischemic regions (Nakagawa et al, 1984). However, other researchers argue that vessels in ischemic regions cannot be further dilated by hypercapnia and, when the surrounding normal vessels dilate in response to CO 2 , the blood flow to the ischemic brain may actually decrease, often referred to as a vascular steal phenomenon (Brian, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Hypothermia increases the latency [11]; in this study, body temperature was maintained within a reasonably narrow range. We minimized fluctuations in end-expiratory carbon dioxide by controlled ventilation in order to avoid the effects of carbon dioxide tension on evoked potentials [12], Premedication was not given and, to minimize the effects of thiopentone, we waited at least 20 min after induction of anaesthesia before recording the VEP. Systemic arterial pressure was maintained within ±25% of the value before operation [13].…”
Section: Discussionmentioning
confidence: 99%
“…The neuroprotective effects of carbon dioxide may also be mediated by reduction of superoxide anion generation and scavenging peroxynitrite, as production of both radicals is known to be increased and to augment brain injury following ischemia (Love, 1999). Moreover, mild hypercapnia (PaCO 2 of 45-70 mm Hg) hastens the post-ischemia recovery of cortical electrical activity (Miller et al, 1980;Nakagawa et al, 1984). Contrarily, Browning et al (1997) demonstrated that increased arterial CO 2 aggravates brain injury in a feline model of focal cerebral ischemia.…”
Section: Carbon Dioxide: Neuroprotective or Neurotoxic?mentioning
confidence: 99%